BiCMOS Colpitts oscillator for vector-sum interpolators. Issue 2 (3rd May 2016) - George, Deepa; Sinha, Saurabh
Abstract : Purpose: The demand for higher bandwidth has resulted in the development of mm-wave phased array systems. This paper aims to explore a technique that could be used to feed the individual antennas in a mm-wave phased array system with the appropriate phase shifted signal to achieve the required directivity. It presents differential Colpitts oscillators at 5 and 60 GHz that can provide differential output signals to the quadrature signal generators in the proposed phase shifter system. Design/methodology/approach: The phase shifter system comprises a differential Colpitts voltage controlled oscillator (VCO) and utilizes the vector-sum technique to generate the phase shifted signal. The differential VCO is connected in the common-collector configuration for the 5-GHz VCO, and is extended using a cascode transistor for the 60-GHz VCO for better stability at mm-wave. The vector sum is achieved using a variable gain amplifier (VGA) that combines the in-phase and quadrature phase signal, generated from oscillator output using hybrid Lange couplers. The devices were fabricated using IBM 130-nm SiGe BiCMOS process, and simulations were performed with a process design kit provided by the foundry. Findings: The measured results of the 5-GHz and 60-GHz VCOs indicate that differential Colpitts VCO could generate oscillator output with good phase noise performance. The simulation results of the phase shifter system indicate that the generation of signals with phases from 0° to 360° in steps of 22.5° was achieved using the proposed approach. A Gilbert mixer topology was used for the VGA and the linearity was improved by a pre-distortion circuit implemented using an inverse tanh cell. Originality/value: The measurement results indicate that differential Colpitts oscillator in common-collector configuration could be used to generate differential VCO signals for the vector-sum phase shifter. The simulation results of the proposed phase shifter system at mm-wave show that the phase shift could be realised at a total power consumption of 200 mW.